Analysis of screw/pedicle-width ratio and accuracy in navigated versus 3D-controlled fluoroscopy-guided pedicle screw placement - Gierse, Jula; Zimmermann, Felix; Grützner, Paul Alfred; Stallkamp, Jan; Vetter, Sven Y.; Mandelka, Leon Eric (Global spine journal, 2025)
Study Design - Retrospective cohort study. - Objectives - Due to the close anatomic relationship between the pedicle and neurovascular structures, avoiding pedicle perforations is crucial in pedicle screw placement. Still, the use of larger screws has biomechanical advantages. Intraoperative 2D and 3D imaging, and navigation guidance can be used to combine both goals. The aim of this study was to compare the screw diameter/pedicle width ratio (SPR) and the screw placement accuracy for 3D controlled fluoroscopy-guided pedicle screw placement vs computer navigated transpedicular screw placement in the thoracic and lumbar spine. - Methods - 200 cases of thoracic and lumbar pedicle screw placement, of which 100 cases were performed using intraoperative computer navigation and 100 cases were performed using fluoroscopy-guidance were retrospectively registered. In the fluoroscopy group, intraoperative 3D scans were performed to confirm implant position and allow for potential intraoperative revision. In addition to accuracy and SPR, demographics, dose reports, and procedure times were analyzed. - Results - Overall, 716 fluoroscopy-guided screws were compared with 740 screws placed using navigation. Screw accuracy (83.2% vs 90.5%; P = .001) and SPR (0.85 ± 0.17 vs 0.88 ± 0.21; P < .001) were significantly higher using navigation compared to fluoroscopic guidance. Furthermore, dose area product (28,545 ± 17,693 vs 20,638 ± 15,856 mGycm2; P < .001), fluoroscopy time (223.6 ± 93.6 vs 92.3 ± 39.7 seconds; P < .001), and procedure time (154.0 ± 81.0 vs 119.7 ± 48.7 min; P = .004) were significantly lower using navigation. - Conclusions - Intraoperative navigation does not only increase the accuracy of pedicle screw placement, but also allows for the placement of larger screws relative to the pedicle width, which may have biomechanical advantages. Notably, contrary to other studies, the use of navigation did not increase patient radiation exposure or procedure time compared to fluoroscopic guidance.